Potential of Binahong Leaves (Anredera cordifolia Ten.) and Shallot Skin (Allium cepa L.) Extract as Biopesticides for Biological Control of Rice Bug (Leptocorisa oratorius F.) - Fenti Wahyu Lestari; Dewi Melani; Zulfaidah Penata Gama (Postgraduate, University of Mataram, 2024)
The rice bug is a pest causing decrease rice production. Meanwhile, binahong leaves and shallot skin contain potential materials for making biopesticides. This research aimed to analyze potential of binahong leaves and shallot skin extract as biopesticides and toxicity tested against rice bug. The research was carried out using Completely Randomized Design, biopesticides were made in various concentrations, 0% as a control; 10; 20; 30; 40; and 50. The extract was calculated for yield, pH, and phytochemical screening. Then, biopesticide sprayed on the pests at 24, 48, 72, 96, 120, 144, and 168 hours to observe mortality, LC50, morphology, behavior, biotic, and data analysis using ANOVA followed 0.05 Tukey test. The results showed the extract has potential as a biopesticide with yield value 8,3 – 12; pH value 4,84 – 5,37; and positive secondary metabolite. Meanwhile, toxicity tests showed the highest mortality at concentration 50%, LC50 at 144th hours and 168th hours was 4,373 and 2,002. Besides that, biopesticides changes morphology and behavior pest. Observations abiotic factors showed that rice bug can survive in temperature range of 22,75 – 25oC and relative humidity of 77 - 84%. In the future, it hoped biopesticides can be commercialized to reduce dependence on chemical pesticides.